EL SACO ROTO DE LA PINTURA RELIGIOSA - Muñoz Clares, Manuel (Imafronte, 1995)
Research on painting in Lorca in the XVII and XVIII centuries, which are being published in the last few years, use to point out the existente of certain meaningful pictorial cycles. Once analised the pictures at the collegiate church San Patricio and those at the town council, both of them linked to the world of battles, we are dealing now with ?he srudy, for a private sphere, of un excepcional exemple: the cycle of Casa de Guevara (Guevara’s house), built by Catnacho Felizes at he end of the XVIII century. It holds a score of pictures of the XVII century, all of them in diferent formats and including alegories of the cardinal virtues, classical and biblical scenes and figures of Saints. The are made according to the taste of Palomino’s treatise and the key explanation of them is the female moral education in accordance with upper class women’s panerns of behaviour in that period.